The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/poms.12167
|View full text |Cite
|
Sign up to set email alerts
|

The Design and Introduction of Product Lines When Consumer Valuations are Uncertain

Abstract: This article presents a model of the design and introduction of a product line when the firm is uncertain about consumer valuations for the products. We find that product line introduction strategy depends on this uncertainty. Specifically, under low levels of uncertainty the firm introduces both models during the first period; under higher levels of uncertainty, the firm prefers sequential introduction and delays design of the second product until the second period. Under intermediate levels of uncertainty th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…A second related literature assumes that firms know demand only up to a parameter [Rothschild, 1974, Lodish, 1980, Aghion et al, 1991, Braden and Oren, 1994, Kalyanam, 1996, Biyalogorsky and Gerstner, 2004, Bergemann and Valimaki, 1996, Aviv and Pazcal, 2002, Hitsch, 2006, Desai et al, 2010, Bonatti, 2011, Biyalogorsky and Koenigsberg, 2014. The modeling approach in these papers assumes that the manager knows the structure of demand and just learns the parameters.…”
Section: Literature On Pricingmentioning
confidence: 99%
See 1 more Smart Citation
“…A second related literature assumes that firms know demand only up to a parameter [Rothschild, 1974, Lodish, 1980, Aghion et al, 1991, Braden and Oren, 1994, Kalyanam, 1996, Biyalogorsky and Gerstner, 2004, Bergemann and Valimaki, 1996, Aviv and Pazcal, 2002, Hitsch, 2006, Desai et al, 2010, Bonatti, 2011, Biyalogorsky and Koenigsberg, 2014. The modeling approach in these papers assumes that the manager knows the structure of demand and just learns the parameters.…”
Section: Literature On Pricingmentioning
confidence: 99%
“…The modeling approach in these papers assumes that the manager knows the structure of demand and just learns the parameters. This could be a two-period model [Biyalogorsky and Koenigsberg, 2014] or an infinite-time model [Aghion et al, 1991]. In the infinitetime model, Aghion et al [1991] consider a very general model where the manager knows the structure of demand up to a parameter (θ), the firms sets prices and observes market outcomes.…”
Section: Literature On Pricingmentioning
confidence: 99%
“…When the levels of demand uncertainty are different, Biyalogorsky and Oded () show that different sequential introduction strategies should be used. Simultaneous introduction should be used only when the level of demand uncertainty is low.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In their paper they considered only a single product. Biyalogorsky and Koenigsberg (2010) extended the study to a product family and showed that when introducing a product line, the optimal introduction sequence depends on the level of demand uncertainty.…”
Section: Introductionmentioning
confidence: 98%
“…The literature in Economics and Marketing also studies product design under demand uncertainty (see Chatterjee andSugita 1990, Biyalogorsky andKoenigsberg 2010). Chatterjee and Sugita (1990) focus on the way demand uncertainty affects competitive new-product introductions.…”
Section: Introductionmentioning
confidence: 99%